Japan Attraction Thought By Students Of Sma Negeri 1 Margaasih (High School) Bandung (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Community Service Program (P2M) is an activity to proceed obligations in Higher Education. This activity is implemented periodically by The Japanese Language Study Program and also other study programs at Widyatama University as a manifestation of the obligation in higher education. This activity is also a medium for The Japanese Language Study Program to contribute education or several social activities to mankind and society which is not only oriented to the internal activities.Japanese, in high schools (SMA), is a cross-interest subject that is given from the beginning to the end of the education period. This is in accordance with the national curriculum issued by the Ministry of National Education. Thus, the ability to communicate in Japanese language is considered important to improve the quality and the motivation to study it. The benefits of Japanese for students can be a provision for continuing studies as well as additional abilities to enter various of work fields. In response to this, The Japanese Language Study Program of Widyatama University Bandung aims to develop and introduce Japanese language and culture by providing knowledge of Japanese language and culture to high school students through Community Service (PKM) activities, which are carried out online in SMA Negeri 1 Marga Asih (High School), Bandung.